Regulation of stable low voltage power supply through phase angle modulation: simulation details - Torla, Ahmad Lutfi; Khan, Sheroz; Abdul Muthalif, Asan Gani (2012)
This paper discusses obtaining further results looking at the implementation of a full-wave rectifier based on phase-modulation. Phase modulation is used to obtain a low-voltage DC supply by controlling phase-angle through changes in a variable resistor and capacitor. This property allows for AC rectification along with an inherent voltage regulation feature. The response of the circuit is recorded in proportion to changes in resistance and capacitance over its range. The ability for the circuit to rectify and regulate is analyzed with respect to its ripple voltage factor which in this paper is recorded as low as 0.25mV/V.